2018
DOI: 10.1002/eap.1672
|View full text |Cite
|
Sign up to set email alerts
|

First signs of macroinvertebrate recovery following enhanced restoration of boreal streams used for timber floating

Abstract: Although ecological restoration generally succeeds in increasing physical heterogeneity, many projects fail to enhance biota. Researchers have suggested several possible explanations, including insufficient restoration intensity, or time-lags in ecological responses that prevent detection of significant changes in short-term monitoring programs. This study aims to evaluate whether benthic macroinvertebrate communities responded to an expanded set of stream restoration measures within a study period of one to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 69 publications
3
14
0
Order By: Relevance
“…; Pilotto et al. ), however, and their results are consistent with ours that indicate the increased breadth of habitat conditions produced by restoration in degraded rivers allowed for the establishment of richer communities with more diverse trait combinations for all studied taxonomic groups.…”
Section: Discussionsupporting
confidence: 91%
“…; Pilotto et al. ), however, and their results are consistent with ours that indicate the increased breadth of habitat conditions produced by restoration in degraded rivers allowed for the establishment of richer communities with more diverse trait combinations for all studied taxonomic groups.…”
Section: Discussionsupporting
confidence: 91%
“…Channelized systems lack larger rock and wood structures which might moderate water currents during high flow events, which might disturb the construction of filtering nets in the case of H. siltalai. Pilotto et al [26] also found that Pisidium spp., in particular, were favored by the enhanced restored sites, with this effect having strengthened with time since restoration. In all the restored sites, but especially the enhanced restored sites, species of shredders and scrapers were more abundant.…”
Section: Macroinvertebratesmentioning
confidence: 92%
“…The negative relationship between the longitudinal variation in depth and macroinvertebrate Shannon diversity appeared driven by the most recently restored sites, which were characterized by the most variation in stream depths in this complexity dimension. This might reflect a time-lag in recovery of macroinvertebrates following the physical disturbance associated with restoration activities, e.g., inputs of large substrate, disturbance of microhabitats including macrophytes [26,30]. Even though the enhanced restoration sites had the most wood, the negative relationship between total volume of instream wood and macroinvertebrate richness likely reflects disturbance from recent enhanced-restoration activities.…”
Section: Macroinvertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…At local scales, the missing zero effect squanders the opportunity to measure future recolonisation of unoccupied sites, through (i) natural processes associated with spatially structured population dynamics (Ovaskainen & Saastamoinen, 2018;Dallas et al, 2020), (ii) rehabilitation of sites following mitigation of threatening processes (e.g. Corlett, 2016;Pilotto et al, 2018), or (iii) as a result of extra-limital processes such as shifting geographic ranges due to climate change and species invasion (e.g. Walther et al, 2009;Hill et al, 2012;Hill et al, 2017;Rabl et al, 2017).…”
Section: The Missing Zero Effectmentioning
confidence: 99%